Combined Liver Resection and Reconstruction of the Supra-Renal Vena Cava: The Paul Brousse Experience - Azoulay, Daniel (2006)
BACKGROUND: Liver tumors with inferior vena cava (IVC) involvement may require combined resection of the liver and IVC. This approach, with its high surgical risks and poor long-term prognosis, was precluded until the development of neoadjuvant chemotherapy, portal vein embolization, reinforced vascular prostheses, and technical advances in liver transplantation. METHODS: We reviewed 22 cases of hepatectomy with retrohepatic IVC resection and reconstruction. The patients had a median age of 51.5 years (range, 32.8–75.3 years). Indications for resection were: liver metastases (n = 9), cholangiocarcinoma (n = 8), hepatocellular carcinoma (n = 2), other cancers (n = 3). The liver resections carried out included 18 first, 3 second, and one third hepatectomy. Segment 1 (caudate lobe) was included in the specimen in 19 cases (86%). Resection concerned 1 to 6 liver segments (median = 5.0). Vascular control was achieved by vascular exclusion of the liver preserving the caval flow (n = 1), standard vascular exclusion of the liver (n = 12), in situ cold perfusion of the liver (n = 9). Ex situ surgery was not necessary in any case. Venovenous bypass was used in 12 cases. The IVC was reconstructed with a ringed Gore-Tex tube graft (n = 10), primarily (n = 8), or by caval plasty (n = 4). A main hepatic vein was reimplanted in 6 cases: into the native IVC (n = 4) or into a Gore-Tex tube graft (n = 2). RESULTS: One patient died (4.5%) due to catheter infection, 7 days after in situ cold perfusion with replacement of the vena cava. Eight patients (36%) had no complications and 14 patients (64%) had 23 complications. In all but 1 case, the complications were transient and successfully controlled. The patients stayed in intensive care for 3.3 ± 2.0 days and in the hospital for 17.7 ± 7.8 days. All vascular reconstructions were patent at last follow-up. With median follow-up of 19 months, 10 patients died of tumor recurrence and eleven were alive with (n = 5) or without (n = 6) disease. Actuarial 1-, 3-, and 5-year survival rates were 81.8%, 38.3%, and 38.3%, respectively. CONCLUSIONS: IVC resection and reconstruction combined with liver resection can be safely performed in selected patients. The lack of alternative treatments and the spontaneous poor prognosis justify this approach, provided that surgery is carried out at a center specialized in both liver surgery and liver transplantation. The development of adjuvant chemotherapy regimens is required to improve the long-term results of this salvage surgery.